Quality control following change of drainage technique of chronic subdural hematomas at Universitetssykehuset Nord-Norge - Eggenheim, Daniel (UiT Norges arktiske universitet, 2020)
Objective: Chronic subdural hematoma is one of the most common neurosurgical conditions affecting the elderly. In March 2016 there was a change in drainage technique at the neurosurgical department, UNN, Norway from a continuous irrigation system to an active drain. This was following a multi-center study conducted by Sjåvik, Bartek, et.al showing fewer complications, with the same recurrence rate as continuous irrigation with an active-drain system. The active drain system is also less resource demanding. The main objective of this study was to compare the rates of recurrences of chronic subdural hematomas after this conversion. Complications, 30-day- and 90-day mortality were secondary end-points. Methods: Patients suffering from cSDH treated with burr-hole evacuation between March 2016 and September 2019 at UNN were included in this study. Patients were identified using the procedure code AAD10. 149 patients were included in the study, making up group A. Patients operated between January 2005 to December 2010 made up group B. These two groups were then compared in terms of baseline characteristics, and primary- and secondary outcomes. Results: Recurrence rate in group A was 16 (10.7%), and 18 in group B (10.8%) (p=0.976). In terms of secondary end-points group A had fewer complications (8.1%) than group B (14.5%) (p=0.074). 30-day mortality were the same between the groups (p=0.862). There was no difference between the groups in 90-day mortality (p=0.151). Conclusions: We found no difference in rates of recurrence after conversion to an active-drain system in march 2016. There was a clear tendency of fewer complications in group A, but no statistical significance. 30-day and 90-day mortality was the same between the two groups. Even though the study found no significant difference in primary-, or secondary-end points, the active-drain system is a technique requiring considerably less resources, while also showing a tendency of less complications.